Pengaruh Doxxing terhadap Perilaku Cyberbullying: Analisis Gender dalam Perspektif Psikologi Forensik - Katili, Rifany Humairah Purnama; Astuti, Suryani Dyah; Artaria, Myrtati Dyah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The development of information technology has transformed social interaction patterns through social media platforms, creating digital aggression phenomena such as cyberbullying and doxxing among adolescents. This study analyzes the influence of doxxing on cyberbullying behavior considering gender factors from forensic psychology perspective. Using cross-sectional survey design, data were collected from 577 high school students aged 15-18 years in Gorontalo Province through stratified random sampling. Research instruments included doxxing questionnaire and Cyberbullying in Social Media Scale analyzed using Structural Equation Modeling-Partial Least Square. Results show doxxing significantly influences cyberbullying in both genders with stronger effects in males, though gender moderation was not statistically significant. From forensic psychology perspective, this study contributes to developing integrative models for digital crime scene analysis and recommends intervention protocols addressing doxxing as gateway behavior.